Applying Suggestopedia Method In Teaching Tenses Simple Past To The Second Semester Students Of English Department At Cokroaminoto Palopo University - Ardhy Supraba (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2021)
This research aims to find out the appropriate way in teaching simple past tense by applying Suggestopedia method and also to find out the students’ participation during the teaching simple past tense by applying Suggestopedia method to the second semester students of English Department of Cokroaminoto Palopo University. The subject of this research is 25 students of the second semester students of English Language Education Study Program, Faculty of Teacher Training and Education, Cokroaminoto Palopo University class B. The result of this research shows that teaching structure simple past tense by applying Suggestopedia method was one of the effective method that was able to enhance the students’ understanding well and easily. It was supported by the achievement of the ideal score in the second cycle. In this case, the mean score in the first cycle was only 66.28 while in the second cycle the mean score was very good 86.6. That mean, the mean score in the second cycle was higher than the mean score in the first cycle. It means that, the students had a good understanding in learning structure simple past tense by applying Suggestopedia method. Meanwhile, the result of observation, the student’s participation in the second cycle was more active 85% than in the first cycle 50%. That mean, the students had a good participation in learning structure simple past tense by applying Suggestopedia method. So, it could be concluded that the Application of Suggestopedia Method in Teaching Simple Past Tense effective in enhancing student’s understanding and also could overcome students’ psychological barriers of the second semester students of Cokroaminoto Palopo University. Thus, it could be clearly concluded that Suggestopedia method is able to enhance students’ understanding in learning structure simple past tense well and easily as fast and intensive as possible.